2018
DOI: 10.15547/bjvm.1010
|View full text |Cite
|
Sign up to set email alerts
|

A serial evaluation of electrocardiographic indices and cardiac arrhythmias during pregnancy, lactation and dry periods in Saanen goats

Abstract: SummarySamimi, A. S., J. Tajik, S. M. Aghamiri & A. Karimi, 2018. A serial evaluation of electrocardiographic indices and cardiac arrhythmias during pregnancy, lactation and dry periods in Saanen goats. Bulg. J. Vet. Med., 21, No 1,[59][60][61][62][63][64][65][66] Aim of this study was to investigate the effects of lactation, pregnancy and dry period on electrocardiographic (ECG) parameters and cardiac arrhythmias in the Saanen goat. A total of twenty female adult clinically healthy Saanen goats 3 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…An animal will be experienced of transportation at least once in their lifetime for one of the purposes of selling, slaughtering, fattening or breeding in sheep production systems (Zhong et al, 2011). The handling, uploading, fasting, confinement, vibration, downloading, changing light condition, poor air quality and mixing of unfamiliar group are kinds of potentials stressors during transport that may cause of physiological stress and behavior changes in sheep (Grandin, 1997;Cockram et al, 2000;Saeb et al, 2010;Samimi et al, 2018). Moreover, Maria et al (2003) and Adzitey (2011) reported that duration and distance, loading density, weather and road condition can be listed as some stressors in livestock during transport.…”
Section: Introductionmentioning
confidence: 99%
“…An animal will be experienced of transportation at least once in their lifetime for one of the purposes of selling, slaughtering, fattening or breeding in sheep production systems (Zhong et al, 2011). The handling, uploading, fasting, confinement, vibration, downloading, changing light condition, poor air quality and mixing of unfamiliar group are kinds of potentials stressors during transport that may cause of physiological stress and behavior changes in sheep (Grandin, 1997;Cockram et al, 2000;Saeb et al, 2010;Samimi et al, 2018). Moreover, Maria et al (2003) and Adzitey (2011) reported that duration and distance, loading density, weather and road condition can be listed as some stressors in livestock during transport.…”
Section: Introductionmentioning
confidence: 99%